Self-perceived depression, anxiety and stress among caregivers of cancer patients in Institut Kanser Negara, Putrajaya during COVID-19 pandemic - Ghazali, Sarah Aqilah (2021)
Background: Cancer incidence continues to rise in Malaysia, and the effect of cancer is profound on the caregivers’ physical, emotional and practical aspects. In addition, the rapid rise of COVID-19 disease has caused many challenges for caregivers as they need to provide immense care with little or no support from healthcare providers nor home care services. As a result, caregivers are likely to exacerbate the symptoms of poor mental health. Objectives: This study aims to determine the prevalence and associated factors of depression, anxiety and stress among caregivers of cancer patients in Institut Kanser Negara (IKN), Putrajaya, during the COVID-19 pandemic. Methodology: A cross-sectional study design using a random sampling method was adopted involving a total of 437 caregivers attending the Radiotherapy and Oncology Department and Palliative Department, IKN. The psychological manifestations were measured using Depression Anxiety Stress Scales and 21 specific items (DASS-21) questionnaires, previously translated and verified. Simple logistic regression and multiple logistic regression analyses were used to address the research question. Results: The most common psychological manifestation among caregivers is anxiety 178 (41.4%), followed by depression 125 (29.1%) and stress 116 (27.0%). The multivariable model indicated that the prevalence of anxiety among caregivers was associated with being female, adjusted odds ratio (Adj OR) = 1.69 (95% CI : 1.13, 2.54; p-value <0.05) while caregivers of the older patients were less likely to be depressed, Adj OR = 0.97 (95% CI : 0.96, 0.99; p-value <0.05). Spousal caregivers were a protective factor for stress, Adj OR = 0.54 (95% CI : 0.32, 0.93; p-value <0.05). Additionally, non-Malay ethnicity were more likely to experience depression, Adj OR = 2.20 (95% CI : 1.34, 3.63; p-value <0.05) and anxiety, Adj OR = 1.82 (95% CI : 1.16, 2.87; p-value <0.05) compared to Malay ethnicity. Finally, caring for patients with poor functional status were more likely to placed them in a considerable poor psychological health outcome of depression, Adj OR = 2.24 (95% CI : 1.10, 4.56; p-value <0.05), anxiety, Adj OR = 3.97 (95% CI : 1.87, 8.42; p-value <0.001) and stress, Adj OR = 3.91 (95% CI : 1.94, 7.90; p-value <0.001). Conclusion: The current study indicates a high prevalence of depression, anxiety and stress among caregivers of cancer patients attending IKN, Putrajaya, during the COVID-19 pandemic. Caregivers who are female, non-Malay ethnicity, caregiving for young and poor performance status patients are at risk of negative psychological health outcomes. Caregivers’ efforts have been invaluable during this pandemic, and they are incredible yet invisible frontline workers. Thus, it is imperative that policymakers acknowledge their valuable contributions and be factored in developing local policies. Future research efforts should focus on developing new intervention methods to reduce psychological risk factors for caregivers during the COVID-19 era.